2011
DOI: 10.1634/theoncologist.2010-0308
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Patients with Advanced Non-Small Cell Lung Cancer Treated in a Phase I Clinic

Abstract: Results. Eighty-five patients (51 men, 34 women) treated on various phase I protocols were identified. The median age was 62 years (range, 30 -85). The median number of previous systemic therapies was two (range, 0 -5). A partial response was observed in eight patients (9.5%) and stable disease lasting >4 months was observed in 16 patients (19%). The median overall survival time was 10.6 months and median progressionfree survival (PFS) time was 2.8 months, which was 0.6 months shorter than the median PFS of 3.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 58 publications
(57 reference statements)
0
5
0
Order By: Relevance
“…We retrospectively reviewed the clinical outcomes of 229 consecutive patients with lung, pancreatic, and head and neck cancers who were treated in the phase 1 clinic at MD Anderson from September 2004 to September 2009. [10][11][12] All patients with these diseases who were treated in the clinic were included. The patients were treated on a total of 57 trials, and we treated anywhere from 1 patient to >20 patients on any given trial.…”
Section: Patientsmentioning
confidence: 99%
“…We retrospectively reviewed the clinical outcomes of 229 consecutive patients with lung, pancreatic, and head and neck cancers who were treated in the phase 1 clinic at MD Anderson from September 2004 to September 2009. [10][11][12] All patients with these diseases who were treated in the clinic were included. The patients were treated on a total of 57 trials, and we treated anywhere from 1 patient to >20 patients on any given trial.…”
Section: Patientsmentioning
confidence: 99%
“…Patients receiving more than five prior treatments had a trend toward shorter survival4. A longer median PFS has been observed in lung cancer patients treated on phase I studies that had received two or less prior therapies compared to lung cancer patients treated with more than two prior therapies5. While it appears that PFS tends to get shorter for a number of factors (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This is the third study to summarize the clinical outcomes of patients with advanced/metastatic NSCLC enrolled in phase I clinical trials [24,25]. Despite the availability of several new therapies, the survival of metastatic NSCLC patients remains dismal.…”
Section: Discussionmentioning
confidence: 99%
“…Among other prognostic factors, the number of prior lines of treatment remained a statistically significant factor for longer survival. Janku et al [24] also identified the ECOG PS score 2 or fewer organ systems involved and the number of prior lines as prognostics factors for survival. Also in their experience, the albumin and LDH rates were not statistically relevant prognostic factors for survival.…”
Section: Discussionmentioning
confidence: 99%